Impact of the addition of azithromycin to antimalarials used for seasonal malaria chemoprevention on antimicrobial resistance of Streptococcus pneumoniae. Issue 12 (13th November 2019) - Hema‐Ouangraoua, Soumeya; Aziz Maiga, Abdoul; Cairns, Matthew; Zongo, Issaka; Frédéric, Nikiema; Serge Yerbanga, Rakiswendé; Tamboura, Boubou; Badji, Henry; Gore‐Langton, Georgia; Kuepfer, Irene; Tinto, Halidou; Sagara, Issaka; et al.
Abstract: Objective: A trial was conducted in Burkina Faso and Mali to investigate whether addition of azithromycin to the antimalarials used for seasonal malaria chemoprevention reduces mortality and hospital admissions of children. We tested the sensitivity of nasal isolates of Streptococcus pneumoniae obtained during this trial to azithromycin and other antibiotics. Methods: Azithromycin or placebo was administered monthly, in combination with the antimalarials used for seasonal malaria chemoprevention, for four months, over the annual malaria transmission seasons of 2014, 2015, and 2016. Nasopharyngeal swabs were collected from 2773 Burkinabe and 2709 Malian children on seven occasions: in July and December each year prior to and after drug administration, and at a final survey in early 2018. Pneumococci were isolated from nasopharyngeal swabs and tested for sensitivity to azithromycin and other antibiotics. Results: A total of 5482 samples were collected. In Burkina Faso, the percentage of pneumococcal isolates resistant to azithromycin among children who had received it increased from 4.9% (95% CI: 2.4%, 9.9%) before the intervention to 25.6% (95% CI: 17.6%, 35.7%) afterward. In Mali, the increase was from 7.6% (95% CI: 3.8%, 14.4%) to 68.5% (95% CI: 55.1%, 79.4%). The percentage of resistant isolates remained elevated (17.7% (95% CI: 11.1%, 27.1%) in Burkina Faso and 19.1% (95% CI: 13.5%, 26.3%) in Mali) among children who had received azithromycin 1 year after stopping the intervention. An increase in resistance to azithromycin was also observed in children who had received a placebo but it was less marked. Conclusion: Addition of azithromycin to the antimalarial combination used for seasonal malaria chemoprevention was associated with an increase in resistance of pneumococci to azithromycin and erythromycin, which persisted 1 year after the last administration of azithromycin. Abstract : Objectif: Un essai a été mené au Burkina Faso et au Mali pour investiguer si l'addition d'azithromycine aux antipaludéens utilisés dans le cadre de la chimioprévention du paludisme saisonnier réduisait la mortalité et les hospitalisations d'enfants. Nous avons testé la sensibilité à l'azithromycine et à d'autres antibiotiques pour les isolats nasaux de Streptococcus pneumoniae obtenus lors de cet essai. Méthodes: L'azithromycine ou un placebo a été administré mensuellement, en association avec les antipaludéens utilisés pour la chimioprévention du paludisme saisonnier, pendant 4 mois, durant les saisons de transmission annuelle du paludisme de 2014, 2015 et 2016. Des échantillons nasopharyngés ont été prélevés sur écouvillons chez 2.773 enfants burkinabés et 2.709 enfants maliens lors de 7 occasions: en juillet et en décembre chaque année avant et après l'administration du médicament, ainsi que lors d'une surveillance finale au début de 2018. Les pneumocoques ont été isolés à partir d'écouvillons nasopharyngés et soumis à des tests de sensibilité à l'azithromycine et à d'autres antibiotiques. Résultats: 5.482 échantillons ont été collectés. Au Burkina Faso, le pourcentage d'isolats de pneumocoque résistants à l'azithromycine chez les enfants qui l'avaient reçu était passé de 4, 9% (IC95%: 2, 4%, 9, 9%) avant l'intervention à 25, 6% (IC95%: 17, 6–35, 7%) après. Au Mali, l'augmentation est passée de 7, 6% (IC95%: 3, 8–14, 4%) à 68, 5% (IC95%: 55, 1–79, 4%). Le pourcentage d'isolats résistants est resté élevé (17, 7% (IC95%: 11, 1–27, 1%) au Burkina Faso et 19, 1% (IC95%: 13, 5–26, 3%) au Mali) chez les enfants ayant reçu l'azithromycine un an après arrêter l'intervention. Une augmentation de la résistance à l'azithromycine a également été observée chez les enfants ayant reçu un placebo, mais elle était moins marquée. Conclusion: L'ajout d'azithromycine à la combinaison antipaludique utilisée pour la chimioprévention du paludisme saisonnier était associé à une augmentation de la résistance du pneumocoque à l'azithromycine et à l'érythromycine, qui persistait un an après la dernière administration d'azithromycine.